Sex-based differences in the association of leisure-time physical activity with the risk of depression: the Ansan and Ansung study of the Korean Genome and Epidemiology Study (KoGES) - Jae Ho Park; Nam-Kyoo Lim; Hyun-Young Park (Frontiers Media S.A., 2023)
ObjectiveDepression is a serious mental disorder which is the leading cause of suicide. This study investigated the association between incident depression and 4-year leisure-time physical activity (PA) levels and/or resistance training (RT).MethodsThis community-based Korean cohort included 3,967 participants without depression at baseline. The average PA-time (the total duration of moderate-intensity leisure-time PA) up to 4 years prior to baseline enrollment was calculated to evaluate the cumulative levels of PA. Participants were divided into four groups based on their average PA-time: "Non-PA," " <150 min/week," "150-299 min/week," and "≥300 min/week." Furthermore, based on compliance to PA guidelines (≥150 min/week of PA-time) and participation in RT, the participants were categorized into four subgroups: "Low-PA," "Low-PA+RT," "High-PA," and "High-PA+RT." A multivariate Cox proportional hazards regression model was used to assess the 4-year incidence of depression according to leisure-time PA levels and/or regularity of RT.ResultsDuring the mean 3.72 ± 0.69 years of follow-up, 432 participants (10.89%) developed depression. In women, performing 150-299 min/week of moderate-intensity leisure-time PA was associated with a 38% risk reduction for incident depression (HR, 0.62; CI, 0.43-0.89; p < 0.05), whereas more than 300 min/week of that was related to a 44% risk reduction for incident depression (HR, 0.56; CI, 0.35-0.89; p < 0.05) as compared to that in the Non-PA group. However, in men, there was no significant relationship between the amount of leisure-time PA per week and the risk of incident depression. Moreover, in both sexes, RT had no significant effect on depression in either the Low-PA or High-PA group.ConclusionsThere was an inverse dose-response association between leisure-time PA levels and incident depression only in women, whereas adding RT to high levels of PA had no significant effect on depression in either sex.